2018
DOI: 10.1002/fsn3.836
|View full text |Cite
|
Sign up to set email alerts
|

Orostachys japonicus induce p53‐dependent cell cycle arrest through the MAPK signaling pathway in OVCAR‐3 human ovarian cancer cells

Abstract: Orostachys japonicus (O. japonicus) is utilized as a traditional medicine for patients with various diseases. This study investigated the effect of the ethyl acetate fraction from O. japonicus extract (OJE) on the growth inhibition of OVCAR‐3 human ovarian cancer cells demonstrated to inhibit cell growth and arrest the cell cycle in OVCAR‐3 cells by blocking the sub‐G1 phase and decreasing cyclin E1/CDK2 expression. Cell cycle arrest was connected to the increased expression of the cell cycle regulating factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…An abnormal cell cycle may lead to the occurrence of a variety of different types of tumor, such as hepatocellular carcinoma (33,34), breast cancer (35), pancreatic cancer (36), ovarian cancer (37) and NSCLC in non-smoking females (38). Wang et al (39) used different microarray expression profiles in their study of primitive neuro-ectodermal tumors, and revealed the same four pathways that were identified in the present study, and several of the same genes in the modules that they identified as being important.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal cell cycle may lead to the occurrence of a variety of different types of tumor, such as hepatocellular carcinoma (33,34), breast cancer (35), pancreatic cancer (36), ovarian cancer (37) and NSCLC in non-smoking females (38). Wang et al (39) used different microarray expression profiles in their study of primitive neuro-ectodermal tumors, and revealed the same four pathways that were identified in the present study, and several of the same genes in the modules that they identified as being important.…”
Section: Discussionmentioning
confidence: 99%
“…The O. japonicus was separated sequentially with organic solvents. These soluble fractions were examined for the effect of anticancer in various cells such as human gastric, hepatoma, colon, ovarian, and pancreatic cancer (Kim, Nam, Kim, Ryu, & Lee, ; Lee, Lee, Kim, Kim, et al, ; Lee et al, ; Lee, Lee, Kim, Suk, et al, ; Ryu, Lee, Kwon, & Lee, ; Ryu et al, ). Among these fractions, EtOAc and DCM extracts exhibited the highest effect for apoptosis signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Fractionated O. japonicus was supplied from a farm in Miryang (Geobugiwasong Ltd.). The O. japonicus was separated using organic solvents, and the extract method was described in the previous studies (Lee, Lee, Kim, Kim, et al, ; Lee, Kim, & Lee, ; Lee, Lee, Kim, Suk, et al, ; Ryu et al, ). Each fraction removed the solvents by evaporator at 40°C to dryness.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, ERK1/2, along with PI3K and p38 signaling pathways, has been shown to promote chondrosarcoma cell motility, invasion and lung colonization (58). The ERK1/2 pathway affects cell cycle progression and apoptosis through the modulation of specific cell cycle regulators expression, including p53 and p21 in OVCAR-3 human ovarian and MCF-7 breast cancer cells (59,60). In the present study, p53 expression was elevated in the HTB94 cells, in a manner dependent on active ERK1/2 signaling.…”
Section: Discussionmentioning
confidence: 99%